Hepatic arterial infusion chemotherapy plus lenvatinib with or without programmed cell death protein-1 inhibitors for advanced cholangiocarcinoma - Wei, Zhanqi; Wang, Yajing; Wu, Boyang; Liu, Ying; Wang, Yaqin; Ren, Zhizhong; Yang, Xiaowei; Chen, Qian; Zhang, Yuewei (Frontiers in Immunology, 2023)
Background: New treatment strategies are needed to improve outcomes for patients with advanced cholangiocarcinoma (CCA) due to the limited efficacy of current firstline chemotherapy regimens. Although the combination of hepatic arterial infusion chemotherapy (HAIC), lenvatinib, and programmed cell death protein-1 (PD-1) inhibitors has been extensively evaluated in the treatment of advanced hepatocellular carcinoma, their roles in advanced CCA remain poorly understood. The purpose of this study is to compare the efficacy and safety of HAIC plus lenvatinib with or without PD-1 inhibitors in patients with advanced CCA.Methods: Between March 2019 to June 2022, patients diagnosed with advanced CAA who received HAIC plus lenvatinib with or without PD-1 inhibitors treatment were reviewed for eligibility. Efficacy was evaluated according to survival and tumor response, and safety was evaluated according to the incidence of adverse events (AEs).Results: Fifty-five patients with advanced CCA were included in the study, and they were divided into the HAIC+lenvatinib (LEN)+PD-1 inhibitors (PD-1i) group (n = 35) and HAIC+LEN group (n = 20). The median follow-up time was 14.0 (5-42) months.Patients in the HAIC+LEN+PD-1i group had significantly better PFS (HR = 0.390; 95% CI 0.189-0.806; p = 0.001) and OS (HR = 0.461; 95% CI 0.229-0.927; p = 0.01) than those in the HAIC+LEN group. The HAIC+LEN+PD-1i group showed a higher objective response rate and disease control rate than the HAIC+LEN group but did not find a significant difference. The incidence of grade 1-2 and grade 3-4 AEs was not significantly higher in the HAIC+LEN+PD-1i group compared to the HAIC+LEN group, whereas two patients (5.7%) in the HAIC+LEN+PD-1i group experienced grade 5 immune-mediated pneumonia.Conclusions: HAIC plus lenvatinib with PD-1 inhibitors is safe and well-tolerated, and has the potential to prolong the survival of patients with advanced CCA. The addition of PD-1 inhibitors may enhance the efficacy of HAIC and lenvatinib.Therefore, the combined therapy has the potential to become a treatment option for advanced CCA.